Founding or transforming?: Social intrapreneurship in three German Christian-based NPOs - Schmitz, Björn; Scheuerle, Thomas (ACRN Journal of Entrepreneurship Perspectives, 2012)
In the increased discussions among scholars about social entrepreneurship, the definitions strongly emphasize innovation, social change and social value creation by using economic means. Although researchers´ definitions of social entrepreneurship do not couple social entrepreneurship to the founding of new organizations, empirical research overemphasizes those leaders that have started a new venture not long ago, often just studying those organizations or persons that have been selected by one of the practitioner groups or fellowship organizations. The effect is a vast neglect of social entrepreneurship within traditional organizations, what is usually called social intrapreneurship. Here we present three German Christian-based NPOs operating in the field of social integration and social services. The paper showcases that there is a vivid, promising and innovative potential within NPOs that is worth being investigated. We would like to contribute to a view that refocuses on well-established organizations as social change agents with high leverage power, high experience (of practices and markets) and a reasonable acquaintance with risk. A research agenda will be presented based on these findings.